1998
DOI: 10.1080/07435809809135530
|View full text |Cite
|
Sign up to set email alerts
|

Association of insulin resistance to electrocardiographic changes in non obese asian indian subjects with hypertension

Abstract: To investigate the relationship between insulin resistance and electrocardiographic changes in hypertension in the absence of confounding influences, plasma glucose and insulin responses to oral glucose were studied in 26 normotensive and 38 hypertensive subjects. Resting ECG was taken and classified into normal or abnormal using the Minnesota code. Among the 38 subjects, 16 had ECG abnormalities. All the hypertensive subjects had normal glucose tolerance. Serum insulin response of hypertensive subjects with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…This age difference between nonobese subjects in the present study and in our previous studies could play a role in causing the different levels of hyperinsulinaemia in the present study. In the present study, hyperinsulinaemia was seen in both the basal state and in the OGTT, whereas in our previous studies on nonobese subjects, 10,11 hyperinsulinaemia was observed only during OGTT. It is not unlikely that hypertension and obesity in¯uence postglucose insulin concentrations independently and possibly confound each other when both are present in the same individual.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…This age difference between nonobese subjects in the present study and in our previous studies could play a role in causing the different levels of hyperinsulinaemia in the present study. In the present study, hyperinsulinaemia was seen in both the basal state and in the OGTT, whereas in our previous studies on nonobese subjects, 10,11 hyperinsulinaemia was observed only during OGTT. It is not unlikely that hypertension and obesity in¯uence postglucose insulin concentrations independently and possibly confound each other when both are present in the same individual.…”
Section: Discussioncontrasting
confidence: 86%
“…We had previously demonstrated the effect of hypertension in causing hyperinsulinaemia in nonobese subjects. 10,11 In the present study, we determined the effect of obesity in normotensive subjects and hypertensive subjects. As a result, the nonobese hypertensive subjects chosen to match the obese group are younger compared to nonobese normotensive subjects (46.9 y vs 55.2 y, Table 1) and both these subjects are still younger compared to nonobese subjects in the previous studies 10,11 (aged 58.6 ± 63.8 y).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention has been given to the adverse health consequences of a moderate increase in body mass index (BMI) in different ethnic groups (2). For example, it was suggested that a moderate increase in BMI makes South Asians more prone to insulin resistance and related diseases (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%